Oud neg.nr. 701083-701119. 'Discussianten ANB-congres. (Diverse portretten, naam op negatief) - Haas, Joh. de,
Oud neg.nr. 701083-701119. 'Discussianten ANB-congres. (Diverse portretten, naam op negatief).